The child Handel - Dicksee, Margaret Isabel, 1859-1903 (artist).:::Creator::::::::::::; Perry, Eugene A. (Eugene Ashton), 1864-1948 (publisher):::Contributor:::::::::::: (Malden, Massachusetts; United States; Eugene A. Perry)
Image of G.F. Handel as a young boy, at the keyboard.